Coastal resource management of Barangay Talokgangan, Banate, Iloilo - Perocho, Ma. Auxilladora B. (2002.)
This paper ilustrates how Coastal Resource Management was implemented in Barangay Talokgangan and how the people themselves were given opportunity and / or responsibility to manage available resources, define their needs, goals and aspirations and make decisions affecting their well-being.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Coastal resource management